Intratonsillar detection of 27 distinct viruses: A cross-sectional study - Silvoniemi A; Mikola E; Ivaska L; Jeskanen M; Loyttyniemi E; Puhakka T; Vuorinen T; Jartti T (WILEY, 2022)
Palatine tonsils have been observed to harbor several distinct respiratory and herpesviruses in separate studies. In this study, the presence of these viruses in palatine tonsils was comprehensively studied in both children and adults. A cross-sectional analysis of 181 patients (median age 22 years; range, 2.6-66) operated for a benign tonsillar disease was conducted. Real-time polymerase chain reaction was performed to detect 27 distinct viruses in all: eight human herpesviruses, 16 respiratory viruses, parvo B19, and polyoma BK/JC viruses. Clinical characteristics of the patients and underlying conditions were evaluated. In total, 92% of patients had virus detected in tonsils (Epstein-Barr virus 72%, human herpesvirus 7, and 6B 54% and 16%, respectively, enterovirus 18%, parvovirus B19 7% and the rest <4%). No herpes simplex virus 2, varicella zoster virus, polyoma JC virus, parainfluenza-, metapneumo-, or coronaviruses were found. Enterovirus was more common in children and was frequently observed in the presence of HHV6B. None of the viruses showed a positive association to the tonsillar disease. Respiratory symptoms were not associated with the prevalence of viruses. This study comprehensively reports a cross-sectional view of intratonsillar virus infections in elective tonsillectomy patients in a wide age range cohort. Tonsils are a major virus reservoir for distinct herpes and respiratory viruses without a positive association with tonsillar disease or respiratory symptoms.